Deconstruction of the Right to Control the State: An Analysis of Article 33 Paragraph (3) of the 1945 Constitution and Its Implications for the Politics of Indonesian Agrarian Law - Umar Ma’ruf; Adhe Ismail Ananda; Cyrilius WT. Lamataro; Mario A. Lawung (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2026)
The concept of the Right to Control the State (HMN) contained in Article 33 paragraph (3) of the 1945 Constitution emphasizes the role of the state in controlling the earth, water, and natural resources for the greatest prosperity of the people. However, the interpretation of HMN in constitutional practice often raises constitutional problems, especially when the state acts more as an absolute owner than as a manager who guarantees the distribution of justice. This article aims to critically analyze the concept of HMN through a constitutional deconstruction approach to uncover the shift in meaning between normative texts and the political practice of agrarian law. Using a normative-juridical research method, this paper explores the contradiction between constitutional idealism and the political reality of agrarian law after the 1960 UUPA, especially in land policy, natural resource management, and agrarian reform programs. The results of the analysis show that Indonesia's agrarian law politics tend to be dominated by state interests and capital, thus obscuring the constitutional mandate related to the prosperity of the people. Therefore, a conceptual reconstruction of HMN is needed so that it is not only understood as the legitimacy of state control, but also as a constitutional mechanism to ensure access, equity, and sustainability of agrarian justice.